Spatial memory is impaired by peripubertal GnRH agonist treatment and testosterone replacement in sheep. (January 2017) - Hough, D.; Bellingham, M.; Haraldsen, I.R.H.; McLaughlin, M.; Rennie, M.; Robinson, J.E.; Solbakk, A.K.; Evans, N.P.
Highlights: Peripubertal GnRHa impaired long-term spatial reference memory. This GnRHa-effect was not counteracted with testosterone replacement in rams. Traverse times of spatial orientation and learning tasks were unaffected by GnRHa. GnRHa exaggerated emotional reactivity during these spatial tasks. Testosterone replacement decreased emotional reactivity and motivation in tasks. Abstract: Chronic gonadotropin-releasing hormone agonist (GnRHa) is used therapeutically to block activity within the reproductive axis through down-regulation of GnRH receptors within the pituitary gland. GnRH receptors are also expressed in non-reproductive tissues, including areas of the brain such as the hippocampus and amygdala. The impact of long-term GnRHa-treatment on hippocampus-dependent cognitive functions, such as spatial orientation, learning and memory, is not well studied, particularly when treatment encompasses a critical window of development such as puberty. The current study used an ovine model to assess spatial maze performance and memory of rams that were untreated (Controls), had both GnRH and testosterone signaling blocked (GnRHa-treated), or specifically had GnRH signaling blocked (GnRHa-treated with testosterone replacement) during the peripubertal period (8, 27 and 41 weeks of age). The results demonstrate that emotional reactivity during spatial tasks was compromised by the blockade of gonadal steroid signaling, as seen by the restorative effects of testosterone replacement, while traverse times remained unchanged during assessment of spatial orientation and learning. The blockade of GnRH signaling alone was associated with impaired retention of long-term spatial memory and this effect was not restored with the replacement of testosterone signaling. These results indicate that GnRH signaling is involved in the retention and recollection of spatial information, potentially via alterations to spatial reference memory, and that therapeutic medical treatments using chronic GnRHa may have effects on this aspect of cognitive function.